Trigeminal Ophthalmic Branch Schwannoma: Case Report and Literature Review - Köhler, Luiza Rech; Mesquita Filho, Paulo Moacir; Santos, Fabio Pires; Sawasaki, Renato; Giacomelli, Richard; Cordeiro, Rafael; Ruschel, Octavio Karam; Schwingel, Daniela (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
Schwannomas are the fourth most common primary neoplasms affecting the brain and cranial nerves. Central lesions commonly arise from sensory nerve roots, and a common intracranial site is the vestibular branch of the 8th nerve (>85%). We present the case report of a patient who has a schwannoma extending from the pterygopalatine fossa to the orbit, complaining about facial pain in the trajectory of the trigeminal ophthalmic branch. Schwannomas represent 1 to 2% of all neoplasms of the orbit, and trigeminal schwannomas are extremely rare, accounting for less than 0.5% of all intracranial tumors.
Keywords: schwannoma; orbital schwannoma; ophthalmic schwannoma; endoscopic transsphenoidal neurosurgery; subciliary approach